PENGARUH PERSEPSI KEMUDAHAN (PERCEIVED EASE OF USE) DAN TINGKAT KEPERCAYAAN TERHADAP PARTISIPASI BERDONASI GEN-Z MENGGUNAKAN PLATFORM CROWDFUNDING DIGITAL TANPA UANG - Nisrina Aulianovanda, Althafa; Ratri Rahmiaji, Lintang; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Generation Z or iGeneration grew up with the internet and made this generation become a cashless society that often uses non-cash systems, one of which is in donating through digital crowdfunding platforms. However, in fact, Generation Z's donation participation still tends to be minimal compared to other generations due to financial problems and trust issues regarding the use of certain donation allocations. Therefore, this study aims to examine whether the perceived ease of use and level of trust affect Gen-Z's donation participation through digital crowdfunding platforms without money. This study is a type of explanatory quantitative research using simple linear regression analysis techniques and non-probability sampling methods, namely purposive sampling with 95 respondents. The results of the study indicate that there is a positive influence between perceived ease of use and the level of trust in Gen-Z donation participation using a digital crowdfunding platform without money. The results and theories used indicate that the influence of variable perceived ease of use on donation participation using the Technology Acceptance Model and Participatory Culture theories shows a moderate influence so that the theory used is quite valid. While the influence of variable level of trust on donation participation using the Fully Functional Society and Participatory Culture theories has a weak effect or the theory is considered invalid to explain its influence. So it can be concluded that the hypothesis tests H1 and H2 are accepted and in line with the Technology Acceptance Model and Participatory Culture theories, but not in line with the Fully Functional Society theory.